SURGICAL MANAGEMENT OF OTOSCLEROSIS- STEPEDECTOMY VERSUS STAPEDOTOMY: Otosclerosis- Stepedectomy versus Stapedotomy - Shah, Maj Amanat Ali; Ahmed, Bashir; Khan, Amir Ali; Rahat, Z.M. (Pakistan Armed Forces Medical Journal, 2010)
Objectives: To compare post operative morbidity after stapedotomy with stapedectomy. Study Design: Quasi-experimental study. Place and Duration of Study: ENT Departments of CMH Rawalpindi and CMH Lahore from Jan 2006 to Jan 2009. Patients and Methods: Forty eight patients were included in this study and were divided into two groups; 14 patients underwent stapedectomy and 34 patients underwent stapedotomy. Results: Severity and duration of vertigo and hospital stay with stapedotomy were less as compared to stapedectomy. Conclusions: These results demonstrated that postoperative morbidity with stapedotomy was less as compared to stapedectomy.